Analysis of Employee Recruitment and Placement Methods at The Gunungsitoli Branch of JNE Express - Boby Rahmat Putra Zebua; Odaligoziduhu Halawa; Ayler Beniah Ndraha (Dinasti Publisher, 2025)
This study aims to analyze the recruitment and employee placement methods at JNE Express Gunungsitoli Branch in order to evaluate their effectiveness in supporting organizational performance within the logistics service sector. The research background is based on the continuing mismatch between applicant qualifications and job requirements, as well as employee placement decisions that are not fully aligned with individual abilities and educational backgrounds. A quantitative descriptive analytical approach was employed, involving all employees as the research sample through a census technique. Data were collected using questionnaires, interviews, and documentation, then analyzed using descriptive statistics supported by thematic interpretation. The results show that the recruitment method is generally well implemented in terms of transparency, fairness, and objectivity, although the suitability of applicant qualifications remains moderate. Employee placement is considered effective in providing clear tasks and balanced workloads, yet alignment between skills, education, and job assignments has not reached an optimal level. The study concludes that recruitment and placement practices at JNE Express Gunungsitoli are adequate for maintaining operational stability but require strategic refinement to ensure stronger competency alignment and long-term performance improvement.